Carbon Pricing and International Competitiveness for Thailand and ASEAN - Tantivasadakarn, Chayun (Thammasat Review of Economic and Social Policy, 2020)
The main purpose of this paper is to provide an economic analysis such that policy makers may decide which carbon pricing measures, between carbon markets or Emission Trading System (ETS) and carbon taxes, would be more appropriate for Thailand based on their impacts on production, consumption, exports, imports, social welfare and international competitiveness. We find that a carbon tax measure that is jointly implemented by five ASEAN countries would be the most suitable for Thailand. This is because it can mitigate carbon dioxide emission to the target level while generating fewer negative impacts on production, consumption, exports, imports, social welfare for Thailand. It also causes less unfavorable economic effects as compared to the case of Thailand’s unilateral carbon tax implementation or the case of carbon market, either unilaterally or jointly. Both carbon taxes and ETS, for the same mitigation target, does not significantly affect Thailand’s international competitiveness. However, a joint carbon tax measure has fewer negative impacts on competitiveness as compared to unilateral implementation and even improves Thailand competitiveness in some sectors.